Analisis Peran Gender Suami Dan Istri Dalam Rumah Tangga Penenun Kain Songket (Studi Kasus Di Kelurahan Tuan Kentang Kecamatan Seberang Ulu 1 Kota Palembang) - Lexi Rosilia; Alfitri Alfitri; Nengyanti Nengyanti (Mahesa Research Center, 2021)
This study aims to analyze and describe gender equality in the household of female songket weavers in Tuan Kentang Village, Seberang Ulu 1 District, Palembang City. This study uses Harvard Analysis. The method used in this research is qualitative research methods. Data collection methods are observation, in-depth interviews and documentation. There are 7 informants in this study. The activity profile includes a description of the reproductive, productive and social division of labor. The access and control profile includes a description of the level of equity in access to resources, access to benefits, control over resources and control over benefits in the household. The results showed that, the household activities profile of women weaving Songket fabrics in Tuan Kentang Village is dominated by activities that are gender biased or have not provided equality for women (including the division of productive labor and the division of social labor). Meanwhile, the division of reproductive labor has a gender perspective in which control of benefits is carried out jointly between male and female. The access and control profile of resources and benefits in the household is generally responsive or women have a high degree of equality in access to and control of resources and benefits.